2017
DOI: 10.1039/c7py00359e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the emission of hexa-peri-hexabenzocoronene-containing polynorbornene via electron donating, unsymmetric constitution and solvent effects

Abstract: Hexa-peri-hexabenzocoronene-containing hydrogenated polynorbornene dispersion showed an intensive emission of the 0–0 transition (465 nm) and excellent dispersibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The HBC also acted as a conjugating core in a hybrid series with benzo[1,2‐ b ;3,4‐ b ]dithiophene as a donor, thieno[3,4‐ c ]pyrrole‐4,6‐dione as an acceptor [244] . Donor‐acceptor interactions were even observed between covalently attached HBC and hexaphenylbenzene, resulting good electroluminescent properties [245] . In addition, hybrid systems featuring peri ‐HBC donor and fullerene acceptor achieved external quantum efficiency of 30% in solar cells [246] .…”
Section: Resultsmentioning
confidence: 99%
“…The HBC also acted as a conjugating core in a hybrid series with benzo[1,2‐ b ;3,4‐ b ]dithiophene as a donor, thieno[3,4‐ c ]pyrrole‐4,6‐dione as an acceptor [244] . Donor‐acceptor interactions were even observed between covalently attached HBC and hexaphenylbenzene, resulting good electroluminescent properties [245] . In addition, hybrid systems featuring peri ‐HBC donor and fullerene acceptor achieved external quantum efficiency of 30% in solar cells [246] .…”
Section: Resultsmentioning
confidence: 99%
“…2a), which is attributed to a reduced symmetry of SB-HBC. 40 Furthermore, the fluorescence quantum yield of SB-HBC was determined to be 0.063, which is higher than the reported values of HBC-tBu (F F = 0.030) and other alkyl substituted HBC derivatives. 41 In contrast to the doubly degenerated HOMO and LUMO of unsubstituted HBC, DFT calculations demonstrated the non-degenerate frontier molecular orbitals (HOMO and LUMO) of SB-HBC, with the electron density shared over the spiro bridge (Fig.…”
mentioning
confidence: 55%
“…Despite the versatility of the ROMP, its synthetic application for the production of polymers with PAH moieties has been rarely investigated. For instance, Liaw et al reported the synthesis of a polymer containing hexa‐ peri ‐hexabenzocoronene (HBC) by ROMP [Scheme (a)] . However, two postmodifications of the poly(norbornene) (PNB) with hexaphenylbenzene (HPB) were required.…”
Section: Introductionmentioning
confidence: 99%